Nanoelectronic device applications handbook - Morris, James E., 1944-; Iniewski, Krzysztof, 1960- (Devices, circuits, and systems., 2013)
"The book has two purposes. First, it assembles the latest research in the field of nanoelectronics device technology in one place. Second, it exposes the reader to myriad applications that nanoelectronics devices technology has enabled. The book is meant for advanced graduate research work or for academicians and researchers. Contributed by world-renowned experts from academia and industry from around the globe, nanoelectronics devices will find widespread application range"--